2019
DOI: 10.21276/apalm.2453
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nucleic Acid Amplification Test (NAT) over Enzyme Linked Immuno Sorbent Assay (ELISA) in Detecting Transfusion Transmissible Infections (TTI) among Blood Donors at a Tertiary Care Centre

Abstract: Background: Background: Blood safety in India becomes prime importance with a large number of blood donors. The donated blood is screened for transfusion transmissible infections (TTI) using immunoassays and nucleic acid amplification Test (NAT). However the risk of infection during window period (WP) might be missed by the immunoassay, which are responsible for most of the TTI. Zero window period might provide complete blood safety.Aim: 1) To study sensitivity, specificity, positive predictive value (PPV), ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…10,12 In a previous study, ELISA, and NAT results of 6,000 donor samples showed that 60 samples were seroreactive while only 52 samples were NAT positive and ELISA negative with one in 113 NAT yield. 14 In another study, ELISA positive, NAT negative (seroyield) samples were as follows, 9 samples seroyield HBV (0.9 %), 9 samples HCV (0.9 %) and 3 samples seroyield HIV (0.3 %). 12 The study by Hans et al, 2019, observed a combined NAT yield for all 3 viruses of 0.09 % (1 in 1,031).…”
Section: Discussionmentioning
confidence: 94%
“…10,12 In a previous study, ELISA, and NAT results of 6,000 donor samples showed that 60 samples were seroreactive while only 52 samples were NAT positive and ELISA negative with one in 113 NAT yield. 14 In another study, ELISA positive, NAT negative (seroyield) samples were as follows, 9 samples seroyield HBV (0.9 %), 9 samples HCV (0.9 %) and 3 samples seroyield HIV (0.3 %). 12 The study by Hans et al, 2019, observed a combined NAT yield for all 3 viruses of 0.09 % (1 in 1,031).…”
Section: Discussionmentioning
confidence: 94%
“…This observation would become a necessity for the implementation of the nucleic acid test (NAT), especially in large transfusion centers in countries with limited resources. And it is preferable for the detection of infectious agents in blood banks to use a NAT with a lower detection threshold (for example 13.2 copies/ml) [ 38 41 ]. HIV-1 strains circulate daily in blood banks, more precisely at the NBTC in Gabon.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown that the consequence of passive blood safety is exposure to infectious agents transmissible by transfusion. To estimate the efficiency of the transfusion chain, it is necessary a priori determine the transfusion risk [41][42][43][44][45]. Today much has been done with the aim of improving the diagnostic tests used in blood banks, but this does not exclude that these tests have limits (existence of the detection threshold) that could be caused by the genetic diversity of HIV-1 whose mutations are seen every day in infected patients.…”
Section: Discussionmentioning
confidence: 99%